A Bacterially Expressed SARS-CoV-2 Receptor Binding Domain Fused With Cross-Reacting Material 197 A-Domain Elicits High Level of Neutralizing Antibodies in Mice - Liqin Liu (Frontiers in Microbiology, 2022)
The Coronavirus disease 2019 (COVID-19) pandemic presents an unprecedented public health crisis worldwide. Although several vaccines are available, the global supply of vaccines, particularly within developing countries, is inadequate, and this necessitates a need for the development of less expensive, accessible vaccine options. To this end, here, we used the Escherichia coli expression system to produce a recombinant fusion protein comprising the receptor binding domain (RBD) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; residues 319–541) and the fragment A domain of Cross-Reacting Material 197 (CRM197); hereafter, CRMA-RBD. We show that this CRMA-RBD fusion protein has excellent physicochemical properties and strong reactivity with COVID-19 convalescent sera and representative neutralizing antibodies (nAbs). Furthermore, compared with the use of a traditional aluminum adjuvant, we find that combining the CRMA-RBD protein with a nitrogen bisphosphonate-modified zinc-aluminum hybrid adjuvant (FH-002C-Ac) leads to stronger humoral immune responses in mice, with 4-log neutralizing antibody titers. Overall, our study highlights the value of this E. coli-expressed fusion protein as an alternative vaccine candidate strategy against COVID-19.